ANALISIS STRATEGI GURU DALAM MENGATASI KECEMASAN BELAJAR PESERTA DIDIK DI ERA MERDEKA BELAJAR DI SEKOLAH DASAR SDN 26 TOLITOLI - Afriansyah; Hamna, S.Pd., M.Pd; Hasia marto (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to analyze teachers' strategies in addressing learning anxiety in elementary school students during the Merdeka Belajar era. This qualitative research employs a case study method. The subjects were class teachers and students at State Elementary School 26 Tolitoli. Data collection techniques were observation, interviews, and documentation. The results showed that teachers implemented various strategies to create a comfortable learning environment, such as individual pedagogical approaches to students, the use of engaging learning media, and the application of enjoyable learning methods. Teachers also faced challenges, such as differences in student characteristics, time constraints, and limited environmental support. Nevertheless, teachers attempted to continuously evaluate and adjust their learning. This study concluded that adaptive teacher pedagogical strategies can reduce student anxiety levels and increase learning motivation. The implication of this study is the need for ongoing training for teachers in recognizing symptoms of learning anxiety and implementing learning approaches appropriate to student characteristics to support the successful implementation of Merdeka Belajar.